Analysis of Employee Job Satisfaction Using a Hygiene Factors Approach at PT PLN NS - M, Andi Surayya; Zainal, Isradi (Green Publisher Indonesia, 2025)
Employee job satisfaction is an important factor that can influence company performance and productivity. Employees who are satisfied with their jobs tend to be more motivated, loyal and have better performance. The aim of this research is to analyze the level of job satisfaction of PT employees. PLN NS with a hygiene factors approach. This research uses quantitative research methods. The data collection technique in this research is a survey conducted online using SOHO Form to facilitate data distribution and collection. Data processing and analysis was carried out using bivariate correlation and the Importance-Performance Analysis matrix. The research results show that the job satisfaction score is in the PUAS range, namely 4.01. Satisfaction scores for each region vary but are within the SATISFIED range. The highest was in the Nusa Tenggara – Maluku – Papua region reaching 4.59 and the lowest in the Kalimantan-2 region reaching 3.58. Meanwhile, the hope for work improvement score is in the PUAS range, namely 3.94. The improvement hope scores for each region are different but are in the SATISFIED range. The highest in the Nusa Tenggara – Maluku – Papua region reached 4.41 and the lowest in the Kalimantan-1 region reached 3.84.